KUR' AN' DA HA VV AN DAVRANIŞLARINA BENZETiLEN iNSAN KARAKTERLERi - Kasapoğlu, Abdurrahman (Fırat University, 2006)
In every society, some abnoımal human behaviours are associated with some kind of animal behaviours. Holy Quran, too, prefers this way in order to explain effectively certain human characters. It makes clear some human characters with the help of comparison between animals !ike donkey, dog, monkey.
Keywords: Religious Studies; Din Araştırmaları